Composite stacks for reliable > 17 T trapped fields in bulk superconductor magnets. (19th December 2019) - Huang, Kai Yuan; Shi, Yunhua; Srpčič, Jan; Ainslie, Mark D; Namburi, Devendra K; Dennis, Anthony R; Zhou, Difan; Boll, Martin; Filipenko, Mykhaylo; Jaroszynski, Jan; Hellstrom, Eric E; Cardwell, David A; et al.
Abstract: Trapped fields of over 20 T are, in principle, achievable in bulk, single-grain high temperature cuprate superconductors. The principle barriers to realizing such performance are, firstly, the large tensile stresses that develop during the magnetization of such trapped-field magnets as a result of the Lorentz force, which lead to brittle fracture of these ceramic-like materials at high fields and, secondly, catastrophic thermal instabilities as a result of flux movement during magnetization. Moreover, for a batch of samples nominally fabricated identically, the statistical nature of the failure mechanism means the best performance (i.e. trapped fields of over 17 T) cannot be attained reliably. The magnetization process, particularly to higher fields, also often damages the samples such that they cannot repeatedly trap high fields following subsequent magnetization. In this study, we report the sequential trapping of magnetic fields of ∼ 17 T, achieving 16.8 T at 26 K initially and 17.6 T at 22.5 K subsequently, in a stack of two Ag-doped GdBa2 Cu3 O7-δ bulk superconductor composites of diameter 24 mm reinforced with (1) stainless-steel laminations, and (2) shrink-fit stainless steel rings. A trapped field of 17.6 T is, in fact, comparable with the highest trapped fields reported to date for bulk superconducting magnets of any mechanical and chemical composition, and this was achieved using the first composite stack to be fabricated by this technique. These post-melt-processing treatments, which are relatively straightforward to implement, were used to improve both the mechanical properties and the thermal stability of the resultant composite structure, providing what we believe is a promising route to achieving reliably fields of over 20 T.